Pengaruh Zat Aditif Mannol Cetane Plus Terhadap Kepekatan Asap Gas Buang Mitsubishi L300 - Isra, Adi; Junaidi, Abdulkhair; Mirfaturiqa, Mirfaturiqa; Rinaldi, Rinaldi; Rahmi, Rahmi; Amsa , Helfany (SURYA TEKNIKA, 2026)
This study aims to analyze the effectiveness of adding the mannol cetane plus additive on exhaust smoke opacity in a Mitsubishi L300 diesel vehicle. A smoke tester was used to measure the density of the exhaust emissions. The results of this test show the effect of reducing smoke density compared to pure B30 biodiesel fuel. With the 5 liter B30 biodiesel variant with 25 ml, the average results are 1000 rpm 0,36%, 1500 rpm 0,53%, 2000 rpm 0,76%, 2500 rpm 1,03%.